Oviposition and development of the gregarious parasitoid Homalotylus eytelweinii (Hymenoptera: Encyrtidae) in relation to host stage of predaceous ladybirds. Issue 4 (3rd April 2022) - Guo, Qi; Meng, Ling; Fei, Minghui; Li, Baoping
ABSTRACT: Though predaceous ladybirds (Coleoptera: Coccinellidae) are known to be attacked by a wide array of parasitoids, the biology of these parasitoids remains largely unknown. This study was focused on the gregarious parasitoid Homalotylus eyteweinii that attacks multiple taxa of predaceous ladybirds, to understand how females allocate brood and their offspring develop in relation to host stage at parasitism with the seven-spot ladybird Coccinella septempunctata as the host. The parasitoid spent the same length of time on ovipositor insertion in response to different host instars. All instars of the host were equally susceptible to parasitism. Parasitism success from oviposition to adult emergence was greater for the 2nd instar than for late instars while similar between the 2nd and 1st instars. Both egg-to-host mummification time and egg-to-adulthood time were longer for the 1st instar than for the late instars. Realised brood size was smaller for the 1st instar host than for the late instars, and there were no differences among the late instars. Sex ratio of realised brood was not significantly different among host instars and was female-biased. Body size of offspring male and female adults at emergence was not significantly different among host instars. These results suggest that middle instars of C. septempunctata are of higher quality for offspring development of H. eytelweinii .